FUS-immunoreactive inclusions are a common feature in sporadic and non-SOD1 familial amyotrophic lateral sclerosis - Deng, Han-Xiang (Ann Neurol, 2010)
OBJECTIVE: Amyotrophic lateral sclerosis (ALS) is a fatal disorder of motor neuron degeneration. Most cases of ALS are sporadic (SALS), but about 5-10% of ALS cases are familial (FALS). Recent studies have shown that mutations in FUS are causal in approximately 4-5% of FALS and some apparent SALS cases. The pathogenic mechanism of the mutant FUS-mediated ALS and potential roles of FUS in non-FUS ALS remain to be investigated. METHODS: Immunostaining was performed on postmortem spinal cords from 78 ALS cases, including SALS (n=52), ALS with dementia (ALS/dementia, n=10) and FALS (n=16). In addition, postmortem brains or spinal cords from 22 cases with or without frontotemporal lobar degeneration (FTLD) were also studied. In total, 100 cases were studied. RESULTS: FUS-immunoreactive inclusions were observed in spinal anterior horn neurons in all sporadic and familial ALS cases, except for those with SOD1 mutations. The FUS-containing inclusions were also immunoreactive with antibodies to TDP43, p62 and ubiquitin. A fraction of tested FUS antibodies recognized FUS inclusions and an unusual antigen retrieval appeared to be important for detection of the skein-like FUS inclusions. INTERPRETATION: Although mutations in FUS account for only a small fraction of FALS and SALS, our data suggest that FUS protein may be a common component of the cellular inclusions in non-SOD1 ALS and some other neurodegenerative conditions, implying a shared pathogenic pathway underlying SALS, non-SOD1 FALS, ALS/dementia and related disorders. Our data also indicate that SOD1-linked ALS may have a distinct pathogenic pathway from SALS and other types of FALS.